2021
DOI: 10.1155/2021/6046184
|View full text |Cite
|
Sign up to set email alerts
|

Multitask Interactive Attention Learning Model Based on Hand Images for Assisting Chinese Medicine in Predicting Myocardial Infarction

Abstract: Acute myocardial infarction (AMI) is one of the most serious and dangerous cardiovascular diseases. In recent years, the number of patients around the world has been increasing significantly, among which people under the age of 45 have become the high-risk group for sudden death of AMI. AMI occurs quickly and does not show obvious symptoms before onset. In addition, postonset clinical testing is also a complex and invasive test, which may cause some postoperative complications. Therefore, it is necessary to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…erefore, teachers need to actively guide students through classroom instruction, use motivating and effective assessments (individual classroom extra credit, group assessment, and music grade percentages), and provide opportunities for students to demonstrate their musical skills in order to create a strong desire to learn creative writing. By constructing an "interactive" learning model, it is clear that students' thinking skills are enhanced and their individual musical perception, participation, confidence, and expression are strengthened [27][28][29][30][31][32][33][34][35]. In terms of knowledge, experience, personality, spirit, culture, etc., the vision is enhanced, life is empathized and experienced, life is enlightened, and spirituality is enriched, and the direction of development of teachers and students tends to the realm of truth and beauty.…”
Section: Encourage Students To Dare To Create Through Learningmentioning
confidence: 99%
“…erefore, teachers need to actively guide students through classroom instruction, use motivating and effective assessments (individual classroom extra credit, group assessment, and music grade percentages), and provide opportunities for students to demonstrate their musical skills in order to create a strong desire to learn creative writing. By constructing an "interactive" learning model, it is clear that students' thinking skills are enhanced and their individual musical perception, participation, confidence, and expression are strengthened [27][28][29][30][31][32][33][34][35]. In terms of knowledge, experience, personality, spirit, culture, etc., the vision is enhanced, life is empathized and experienced, life is enlightened, and spirituality is enriched, and the direction of development of teachers and students tends to the realm of truth and beauty.…”
Section: Encourage Students To Dare To Create Through Learningmentioning
confidence: 99%
“…Several diagnostic models have been developed based on artificial intelligence (15)(16)(17)(18). Du et al reported that a system model based on improved machine learning showed a certain effect in their clinical analysis of AMI (17).…”
Section: Discussionmentioning
confidence: 99%
“…Du et al reported that a system model based on improved machine learning showed a certain effect in their clinical analysis of AMI ( 17 ). Wang et al established a multitask interactive attention learning model and found it could improve the diagnostic efficiency of AMI ( 18 ). However, privacy security risks have hindered the development of artificial intelligence-based diagnostic models in AMI and other diseases.…”
Section: Discussionmentioning
confidence: 99%